The effectiveness of humanitarian aid in conflict zones: practitioner views on the transition from in-kind assistance to multi-purpose cash transfers - Dani Grané Alsina; Derek Eldridge (Journal of International Humanitarian Action)
Abstract The views of humanitarian practitioners in Somalia, South Sudan, Tigray and Yemen are gathered to enlarge understanding on the extent to which multi-purpose cash transfers (CTs) are superseding in-kind assistance in meeting the needs of beneficiaries. The reasons for the choice between the two forms of assistance are exposed together with the identification of the constraints faced when planning and delivering aid in the context of on-going conflict. Key areas of concern for agencies are identified on achieving effective targeting, ensuring internal arrangements support cash transfers, maximising coordination between agencies, upholding human dignity and enhancing the role of women as beneficiaries. Overall, the findings suggest that multi-purpose cash transfers can be an effective form of assistance in conflict zones, and recommendations are made for agencies as they contemplate an expansion of this form of assistance.